Crystal growth vs. conventional acid etching: A comparative evaluation of etch patterns, penetration depths, and bond strengths - Devanna Raghu; Keluskar K (Wolters Kluwer Medknow Publications, 2008)
The present study was undertaken to investigate the effect on enamel surface, penetration depth, and bond strength produced by 37% phosphoric acid and 20% sulfated polyacrylic acid as etching agents for direct bonding. Eighty teeth were used to study the efficacy of the etching agents on the enamel surface, penetration depth, and tensile bond strength. It was determined from the present study that a 30 sec application of 20% sulfated polyacrylic acid produced comparable etching topography with that of 37% phosphoric acid applied for 30 sec. The 37% phosphoric acid dissolves enamel to a greater extent than does the 20% sulfated polyacrylic acid. Instron Universal testing machine was used to evaluate the bond strengths of the two etching agents. Twenty percent sulfated polyacrylic acid provided adequate tensile bond strength. It was ascertained that crystal growth can be an alternative to conventional phosphoric acid etching as it dissolves lesser enamel and provides adequate tensile bond strength.